RELIGIOUS FREEDOM IN COMMUNIST ROMANIA REGARDED BY THE GENERAL STATUS OF RELIGION DECREE OF 1948 (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2022)
Freedom of religion and conscience are one of the fundamental human rights,enshrined in human nature, but also legally established over the years throughvarious laws, treaties and international conventions, to which Romania is aparty. An analysis of the General Status of Religion Decree of 1948, whichestablished relations between the state and the denominations for more thanhalf a century, will highlight the state’s desire to promote the idea of religiousfreedom, which the same state will not apply. The discrepancy between legislativespeech and daily reality has often been accused in times by those whofelt the law’s failure.